Integrasi Sistem Manajemen Pergudangan dengan Sistem Akuntansi dalam Aplikasi ERP - Leander, Andre; Wibowo, Adi; Dewi, Lily Puspa (Jurnal Infra, 2014)
ERP application is an application that capable to integrate various systems within a company. Warehouse Management System and Accounting System are two different systems but interconnected. Accounting Systems becomes the center of a variety of enterprise systems so that any transactions that occur in other systems such as Warehouse Management System is controlled by Accounting System. The problem that arises is each system uses different applications so to make the two systems work separately.The application development begins with analyzing the processes that occur, the technologies are used, stakeholders, and business rules in Warehouse Management System and Accounting System. In the next phase, undertake the design of integrated system of analysis results. The design phase results in a number of modeling used to develop the application.At the of application development phase produces an ERP application that has two integrated modules that warehouse management module that manage Warehouse Management System and accounting module that manage the Accounting System.